PROGRAM KAMPUS MENGAJAR ANGKATAN IV SEBAGAI UPAYA MENINGKATKAN KEMAMPUAN LITERASI DAN NUMERASI SD NEGERI 40 MACOPPE - Ayu Andira (Jurusan Pendidikan Guru Sekolah Dasar Kampus VI Bone, 2024)
This fourth generation teaching campus is one form of implementing MBKM in the form of teaching assistance in educational units to empower students to help with 4 important aspects in elementary schools and junior high schools, namely helping to improve literacy and numeracy, administrative assistance, and assistance with technology adaptation. The implementation of the fourth generation teaching campus program was carried out at SD Negeri 40 Maccope which is located in Maccope Village, Awangpone District, Bone Regency, South Sulawesi Province, which was carried out from August to December 2022. The Teaching Campus Team at SD Negeri 40 Maccope itself consisted of six people and in accompanied by a field supervisor. In making the Teaching Campus agenda a success, the Teaching Campus Team at SD NEGERI 40 MACCOPE focuses on four main programs, namely, Adaptation of Technology for Teachers and Students, Tutoring (Literacy and Numeracy), Implementation of Ceria Gymnastics and Procurement of Porseni. All assistance has been implemented and received a positive response from teachers and the local community